Presence of hyphae in chromoblastomycosis examinations: an enigma to be solved - Gustavo de Sá Menezes Carvalho; Karina Baruel de Camargo Votto Calbucci; Rute Facchini Lellis; John Verrinder Veasey (Sociedade Brasileira de Dermatologia, 2021)
Abstract The detection of muriform cells in direct mycological or anatomopathological examination is considered pathognomonic for chromoblastomycosis. The morphological aspect that these fungal structures acquire were called "Borelli spiders", when associated with hyphae. Reports of this association have been described for decades, initially related to more pathogenic agents of this mycosis. More recent studies have shown aspects related to the host's immunity that participate in this process, as well as an association with a worse disease prognosis. The present study discloses the findings of complementary examinations with the presence of "Borelli's spiders" in a patient diagnosed with chromoblastomycosis.